'Independence' and the Founding of the Federal Reserve. - Forder, J (2003)
The Federal Reserve is "independent", but contrary to opinions often expressed, it was not intended by its creators to be free from political control, although others involved in the debate over its establishment hoped that it would be. "Independence" was independence from banking interests, not government. A gradual development of independence preceded a much greater acquisition of power during the Reagan Presidency. The lessons of history include the fact that with few changes in the Federal Reserve Act, its position in the American government has been dramatically transformed. Consequently, contrary to common practice in the economics literature, the "independence" (from government) of a central bank evidently cannot be measured by tabulating characteristics of its statutes.